2014
DOI: 10.1007/s11748-014-0492-9
|View full text |Cite
|
Sign up to set email alerts
|

Technical aspects of mitral valve repair in Barlow’s valve with prolapse of both leaflets: triangular resection for excess tissue, sophisticated chordal replacement, and their combination (the restoration technique)

Abstract: Initial experience with the restoration technique has provided excellent results without significant systolic anterior motion. Our technique may contribute to improve late results in Barlow's valve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Another important observation of this meta-analysis was that overall surgical volume (ie, number of patients) did not appear to influence early or late surgical outcomes. Comparing six low-volume studies (arbitrarily defined as fewer than 50 cases; one minimally invasive, 23 four sterntomy 7,8,13,19,20 ) with the rest of the cohort, there was no apparent effect of volume on the primary outcome in the meta-regression analysis.…”
Section: Random Effects Modelmentioning
confidence: 96%
See 1 more Smart Citation
“…Another important observation of this meta-analysis was that overall surgical volume (ie, number of patients) did not appear to influence early or late surgical outcomes. Comparing six low-volume studies (arbitrarily defined as fewer than 50 cases; one minimally invasive, 23 four sterntomy 7,8,13,19,20 ) with the rest of the cohort, there was no apparent effect of volume on the primary outcome in the meta-regression analysis.…”
Section: Random Effects Modelmentioning
confidence: 96%
“…Of 1122 articles that were retrieved for evaluation, 18 met the inclusion criteria, including one randomized controlled trial, one propensity score matching study, 11 single-arm sternotomy studies, and five single-arm minimally invasive studies (Supplemental Figure 1). 7,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] There was 100% concordance between reviewers equating to a Cohen's k of 1. The mean sample size was 92.5 patients (range, 12 to 250) and the mean follow-up duration was 51.6 months (range, 14 to 138).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Some reports have suggested a relationship between BD and mitral annular disjunction, and Hiemstra et al [ 6 ] reported annular remodeling and stabilization as being important for the surgical treatment in BD in order to correct the dilation and abnormal annulus movement. Miura et al [ 7 ] reported a restoration technique that involved reducing the lateral volume of excess leaflets in the rough zone and correcting the prolapse using a few artificial chordae. Therefore, we followed the MVr strategy according to these concepts of fixing the MV by annuloplasty, reducing excess volume by resection, and correcting the prolapse with artificial chordae, and we controlled MR without causing residual MR, MS, or SAM.…”
Section: Discussionmentioning
confidence: 99%
“…It is important not to try to resect all segments which appear prolapsed because the Barlow's valve often lacks the normal reference and therefore contains the risk of excessive resection. The main purpose of the leaflet resection is to optimize the leaflet volume and restore the symmetrical shape rather than eliminate all the prolapsed segments 8 . Therefore, additional neochord implantation is sometimes necessary to correct the residual prolapse or to correct the position of the PML, which often deviates anteriorly and may promote SAM.…”
Section: Discussionmentioning
confidence: 99%